2016
DOI: 10.1007/82_2016_18
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathogenesis of Chlamydial Infections

Abstract: Chlamydial infections lead to a number of clinically relevant diseases and induce significant morbidity in human populations. It is generally understood that certain components of the host immune response to infection also mediate such disease pathologies. A clear understanding of pathogenic mechanisms will enable us to devise better preventive and/or intervention strategies to mitigate the morbidity caused by these infections. Over the years, numerous studies have been conducted to explore the immunopathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 157 publications
(204 reference statements)
0
18
0
Order By: Relevance
“…trachomatis [ 51 ]. Studies in animal models also suggest CD8 T cells and other immune mechanisms play a major role in Chlamydia -induced upper tract pathology, including infertility [ 47 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…trachomatis [ 51 ]. Studies in animal models also suggest CD8 T cells and other immune mechanisms play a major role in Chlamydia -induced upper tract pathology, including infertility [ 47 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these disease sequelae were not induced by C. trachomatis infection in mice or guinea pigs and therefore we have not been able to confirm the efficacy of the vaccine against the human pathogen. In this context, we noted that CPAF is a highly conserved chlamydial protein, and a strong association between C. pneumoniae and exacerbation of atherosclerosis in human individuals, and a cause-and-effect relationship in mice and rabbits has been demonstrated 1 . We have now demonstrated that rCPAF±IL-12 vaccination significantly attenuates C. pneumoniae -induced exacerbation of atherosclerosis in the C57BL/6 male mouse model.…”
Section: Discussionmentioning
confidence: 85%
“…High c-hsp60 antibody titres in koalas have been associated with fibrous occlusion of the uterus or uterine tube, however their role in chlamydial pathogenesis in koalas remains unclear as they were also associated with lower levels of active inflammation and fewer chlamydial inclusions 28 . Human studies suggest that although the Class II MHC defined anti-chlamydial antibody response appears to be important for chlamydial clearance and c-hsp60 antibodies are protective, it does not always prevent pathology 29,30 .…”
Section: Discussionmentioning
confidence: 99%